2015
DOI: 10.1177/2050312115580799
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy intervention in patients with non-cardiac chest pain following a recent cardiac event: A randomized controlled trial

Abstract: Objectives:To assess the effect of two different physical therapy interventions in patients with stable coronary heart disease and non-cardiac chest pain.Methods:A randomized controlled trial was carried out at a university hospital in Norway. A total of 30 patients with known and stable coronary heart disease and self-reported persistent chest pain reproduced by palpation of intercostal trigger points were participating in the study. The intervention was deep friction massage and heat pack versus heat pack on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The initial search retrieved 15,071 studies, from which 37 RCTs26,37–72 involving a total sample of 1574 participants aged from 18 to 76 years were included in this NMA (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The initial search retrieved 15,071 studies, from which 37 RCTs26,37–72 involving a total sample of 1574 participants aged from 18 to 76 years were included in this NMA (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Specific cardiovascular sequelae of Long COVID Syndrome may benefit from massage therapy, which can ameliorate chest pain; ( 57 , 58 ) however, there were no studies within our selection criteria demonstrating the relationship between massage therapy and palpitations. While the exact mechanism of chest pain in the context of Long COVID Syndrome is not yet clear, elevated concentrations of C-reactive protein (CRP) and creatine during acute COVID-19 infection have been associated with prolonged cardiovascular symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Berg et al[ 18 ] found in a randomized controlled trial that treatment with deep friction massage with heat pack was significantly more efficient than heat pack alone to decrease musculoskeletal chest pain. Healthrelated quality of life scores showed no differences between groups.…”
Section: Discussionmentioning
confidence: 99%